Verb naming fluency in hypokinetic and hyperkinetic movement disorders. (March 2018) - Bayram, Ece; Akbostanci, Muhittin C.
Abstract: Cortical motor regions are considered to play a role in action related language. These regions are affected differently in different types of movement disorders. Parkinson's disease, a hypokinetic movement disorder, has been shown to cause action language disruptions alongside movement deficits. Action language, however, has not been investigated in primary cervical dystonia, a hyperkinetic movement disorder. The aim of this study is to investigate whether action language is affected differently in hypokinetic and hyperkinetic movement disorders which have different effects on movements. Thirty patients with Parkinson's disease, thirty primary cervical dystonia patients and thirty healthy controls were included in the study. Participants performed phonemic, semantic and action fluency tasks. Verbs produced during action fluency were grouped as action and non-action verbs and group differences were investigated. Our results showed that all participants performed similarly in all of the fluency tasks. Mean action content of the verbs produced in action fluency did not differ between groups. During action fluency, however, whereas healthy controls produced more action verbs than non-action verbs, both patient groups did not have this difference between verb groups. Primary cervical dystonia patients produced less action verbs compared to healthy controls. The lack of action language deficits in Parkinson's disease and only an action verb deficit in primary cervical dystonia without any other action language deficits reject strong embodiment.